The effect of leadership styles during the strategy development process and environmental conditions on organizational agility - Nazif, Tannaz Khoshahval (My University, 2022)
Bu araştırmada, strateji oluşturma sürecindeki liderlik stilleri ile çevresel faktörlerin Örgütsel çevikliğin üzerine etkisi incelemektedir. Araştırmada, liderler şirketlerde stratejiler oluştururken oluşan liderlik stillerini inceliyor. Sonuç, birçok farklı sektörde faaliyet gösteren 320 Türk yönetici arasında araştırıldı. Bunu ölçmek için Likert ölçeğine dayalı 48 soruluk bir anket tasarlanmıştır. Sonuçlar SPSS'de test edildi. Sonuçlar, strateji oluşturma sürecindeki liderlik stillerinin ve çevresel koşulların Örgütsel Çeviklik üzerinde olumlu bir etkiye sahip olduğunu göstermiştir. Ayrıca sonuçlar, yöneticiler ne kadar işlemci ve güç verici olursa, şirketler de o kadar çevik olacağı gerçeğini ifade eder. Ayrıca çevrenin “Cömertliği” nin de Örgütsel Çevikliği olumlu yönde etkilediği belirlenmiştir.

This research investigates into the effects of leadership styles during the strategy-making process and environmental factors on Organizational agility. The research draws on leadership styles that are formed when leaders are making strategies in the organization. The result has been investigated among 320 Turkish managers active in many different sectors. To measure this, a 48-question questionnaire was designed based on Likert scale. Results indicated that the leadership styles during the strategy making process and environmental conditions have a positive effect on Organizational Agility. Also results articulate the fact that, the more transactive and generative the managers are, the more the organization will be agile. In addition, ‘Munificence’ of the environment has determined to effect OA positively.
Strateji geliştirme sürecinde liderlik stilleri ve çevresel koşulların örgütsel çeviklik üzerine etkisi
Keywords: Business; Çevresel koşullar; environmental conditions; İşletme; Leadership styles; Liderlik stilleri; Organizational Agility; Örgütsel çeviklik; Strategy making process; strateji geliştirme